Mechanical Properties of Banana Peduncle Fiber Ropes - Nur, Christmastuti; Djati, Imam Damar; Widiawati, Dian (Jurnal Sains Materi Indonesia, 2025)
Banana plants are utilized in almost all parts except for the peduncle due to their hardness and the presence of gum. This research, aimed at evaluating the mechanical properties of banana peduncle fiber, particularly its tensile strength, is significant in exploring the potential of this underutilized part of the plant. The tensile test followed the SNI 12-0064-1987 standard to assess and compare Manila and sisal ropes. Six types of fiber were tested: bleached peduncle fiber, unbleached peduncle fiber, abaca (Manila) fiber, coir fiber, marketed abaca fiber, and marketed coir. The highest average maximum load was found in marketed abaca rope, which measured 346.7 kg. However, this is still below the minimum load standard required by SNI, which is 480 kg. The results of the marketed abaca differ from those of abaca ropes spun using a foot spindle, indicating that the spinning and twisting techniques significantly influence tensile test outcomes. The test also shows that the bleaching process weakens the fiber strength because the unbleached banana peduncle ropes reach a higher average maximum load (92.9 kg) than the bleached banana peduncle ropes (45.2 kg). Moreover, the tensile strength tests revealed that the average breaking load of banana peduncle fiber rope was 92.9 kg, comparable to abaca fiber at 93.7 kg and coir fiber at 92.8 kg. This comparison was based on similar variables: a diameter of 8 millimeters, similar spinning techniques using a foot spindle, and no prior bleaching process. These findings underscore the potential of underutilized banana peduncle fiber ropes as a promising alternative to abaca or coir due to their load-bearing capabilities. It is important to note that the results of this tensile test are comparative rather than absolute.